Legal Reconstruction of Tax Collection on Crypto Assets and Non-Fungible Tokens (NFT) in the Perspective of Legal Certainty and State Financial Revenue - Khofifah Pane; Irwan Triadi; Mas Punky Hendra Wijaya (Catalist Indo Publisher, 2026)
Indonesia's crypto asset and Non-Fungible Token (NFT) ecosystem has grown at a pace that substantially outstrips its regulatory readiness. By early 2025, the number of domestic crypto users had reached 22.9 million accounts, with total transaction value throughout 2024 amounting to IDR 650.61 trillion — positioning Indonesia as one of Southeast Asia's largest crypto markets. Against this backdrop, cumulative tax revenue from the sector stood at only IDR 1.19 trillion since 2022, falling far short of its actual fiscal potential. This study examines two core issues: first, how the legal construction of crypto asset and NFT taxation stands up to scrutiny under the principle of legal certainty in tax law; and second, whether the current tax collection mechanism adequately satisfies the principles of equity and efficiency as instruments of state revenue. Employing normative legal research with statutory and conceptual approaches, this study finds that Indonesia's crypto tax framework contains significant normative gaps, most notably the absence of any specific legal basis governing NFT taxation. The successive amendments from PMK 68/2022 through PMK 81/2024 to PMK 50/2025 reflect an adaptive effort that remains incomplete. From a fiscal equity perspective, the flat-rate Final Income Tax scheme is inconsistent with the ability-to-pay principle, as it treats small and large investors identically. This study concludes that statutory-level regulation explicitly addressing NFTs is urgently needed, alongside a shift toward a more equitable rate structure.